2021
DOI: 10.21577/0103-5053.20210112
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition of Dipteryx alata Vogel Pulp + Peel and Its Antioxidant and Cytotoxic Properties

Abstract: Dipteryx alata Vogel is a native fruit from Brazil, which has been poorly investigated concerning its phenolic composition and the biological effects of its pulp + peel. Thus, in this study we evaluated the antioxidant activity and total phenolic content of the D. alata pulp + peel extracts obtained with different solvents, as well as determined the phenolic compounds by ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) analysis. In addition, cytotoxic effects of D. alata pulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a study with extracts from the epicarp + mesocarp (residues) of Dipteryx alata by ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS), eighteen phenolic compounds were quantified for the first time, predominantly luteolin and trans-cinnamic acid [56]. These results indicate that species of the Dipteryx genus can be explored as a natural source of phenolic compounds with promising properties.…”
Section: Discussionmentioning
confidence: 98%
“…In a study with extracts from the epicarp + mesocarp (residues) of Dipteryx alata by ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS), eighteen phenolic compounds were quantified for the first time, predominantly luteolin and trans-cinnamic acid [56]. These results indicate that species of the Dipteryx genus can be explored as a natural source of phenolic compounds with promising properties.…”
Section: Discussionmentioning
confidence: 98%
“…No studies were identified quantifying the contents of total phenolics, tannins, flavonoids, and flavonols in extracts of D. alata leaves. However, Barizão et al (2021) analyzed hydroalcoholic extracts of the pulp and peel of D. alata fruit, finding higher values of phenolic compounds (3.15 ± 0.14 and 2.98 ± 0.01 mg GAE/g) for ethanol and methanol solvents, respectively. These values were lower than those presented by the UCE (50.00 ± 2.5 mg GAE/g), which was the lowest result obtained in this study.…”
Section: Content Of Total Phenolic Compounds Tannins Flavonoids and F...mentioning
confidence: 97%